Plato on Justice as Harmony - Sumegha Goyal (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2019)
It discusses Plato’s conception of justice. Justice, for Plato, is teleologically linked with goodness and consists of the harmony of the three parts of the soul i.e. reason, spirit, and appetite. Through the series of discussions between Socrates and Thrasymachus, Plato unveils Socrates' definition of justice.